People participating in the 1986 y-Walk - Brock, Trish (photographer):::Creator::::::::::::
Negative shows a large group of men and women participating in the 1986 y-Walk at the corner of Almaden Boulevard and West Santa Clara Street in downtown San Jose. Some of them are carrying balloons and are wearing tee shirts that read: "Walk for women. YWCA 1986." The street sign at the cross walk where the participants are reads: " Almaden Bl." The corner sidewalk that they are coming from is a boarded walkway.